Factors Influencing Milk Yield Characteristics in Bunaji and Friesian x Bunaji Cows in Northern Nigeria - Alphonsus, C; Essien, IC; Akpa, GN; Barje, PP (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
This study was conducted to determine the effect of hemoglobin(Hb) type, breed, sex and season of calving on milk yield characteristics of Bunaji and Friesian x Bunaji cows. The experimental animals consisted of 24 Bunaji and 26 (F1) cross bred (Friesian x Bunaji) cows. The milk yield characteristics were initial milk yield (IMY), end of lactation yield (ELY), peak yield (PY), total milk yield (TMY), and lactation length (LL). The mean values of the milk yield characteristics were 13.69 kg, 61.25 kg, 10.87 kg, 1740 kg and 325.92 days for IMY, PY, ELY, TMY and LL, respectively. These milk yield characteristics were highly variable, with their CV ranging from 11.60 (LL) to 83.00 (IMY). Hb-type significantly influenced milk yield characteristics of the cows. The HbAA was superiorin IMY, PY and TMY compared to HbAB and HbBB. The HbABwas superior in ELY, while HbBB had the longest LL of 343 days. Breed significantly influenced milk yield characteristics except IMY. The Friesian x Bunaji cows were superior to Bunaji in allthe milk yield characteristics. Sex of calves had significant effecton IMY, and LL but not on PY, ELY and TMY. Cows bearing female calves were superior to cows bearing male calves in IMY, while cows with male calves had longer LL. Season of calving significantly affected the milk yield characteristics of cows. Early wet season was superior in IMY and PY, while late wet season had higher PY, ELY, and LL. The TMY was higher and statistically the same in both early wet and late wet season, while the early dry season had the least TMY. In view of the significant influence ofÂ these factors on milk yield characteristics of these cows it is therefore important to take them into consideration in any selection programme aim at improving the milk yield characteristics of the cows.Key Words: Bunaji, Friesian, hemoglobin, milk yield characteristicsAnimal Production 13(3):143-149 (2011)